Electric Vehicle Flexibility Harnessing Through Local Energy Community Operation Optimization: Maximizing Local Energy Utilization - Da Silva, Enielma Cunha [UNESP]; Sabillon, Carlos; Venkatesh, Bala; Franco, John Fredy [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2024)
With an uprising penetration, local energy communities (LECs) face the local challenge of reaching energy self-sufficiency (catering for high generation-demand time mismatch) and the system-wide challenge of securely operating within the distribution network. In this sense, a novel strategy for LEC operation is proposed to overcome these challenges, aiming to maximize local consumption by controlling the charging/discharging of EVs and exploiting distributed generation resources at full, guaranteeing a distribution system secure operation. For this, the local operation of LECs (encompassing conventional and flexible demand members and prosumer members) is represented by a mixed-integer linear programming model, also considering the LEC interaction with the distribution network, and distribution system technical limits. To validate the proposed strategy, the impact of the economic interaction among LECs as well as EV charging/discharging control on LECs' self-consumption, was analyzed in a case study under different operation conditions. The numerical results demonstrate that, when compared to the baseline scenario, EV charging/discharging coordination enabled the local supply of 80.5% of the LECs' daily energy, increasing to 88.31% when the interaction between LECs is enabled.
Keywords: Electric Vehicle; Flexibility; Local Energy Communities; Peer-to-Peer